Exercise-induced leg pain - Davide Edoardo Bonasia; Federica Rosso; Umberto Cottino; Roberto Rossi (Elsevier, 2015)
Exercise-induced leg pain is a common condition in athletes and in people involved in recreational sports. The diagnosis is not always straightforward: many conditions may cause exercise-induced leg pain. The aim of the present review is to provide a complete discussion of the most common pathologies related to this condition. Particular attention is dedicated to the history and the physical examination, which are fundamental for requesting the correct diagnostic tests or imaging techniques necessary for a precise diagnosis.